On the origin of the marine zinc–silicon correlation - de Souza, G; Khatiwala, S; Hain, M; Little, S; Vance, D (Elsevier, 2018)
The close linear correlation between the distributions of dissolved zinc (Zn) and silicon (Si) in seawater has puzzled chemical oceanographers since its discovery almost forty years ago, due to the apparent lack of a mechanism for coupling these two nutrient elements. Recent research has shown that such a correlation can be produced in an ocean model without any explicit coupling between Zn and Si, via the export of Zn-rich biogenic particles in the Southern Ocean, consistent with the observation of elevated Zn quotas in Southern Ocean diatoms. Here, we investigate the physical and biological mechanisms by which Southern Ocean uptake and export control the large-scale marine Zn distribution, using suites of sensitivity simulations in an ocean general circulation model (OGCM) and a box-model ensemble. These simulations focus on the sensitivity of the Zn distribution to the stoichiometry of Zn uptake relative to phosphate (PO4), drawing directly on observations in culture. Our analysis reveals that OGCM model variants that produce a well-defined step between relatively constant, high Zn:PO4 uptake ratios in the Southern Ocean and low Zn:PO4 ratios at lower latitudes fare best in reproducing the marine Zn–Si correlation at both the global and the regional Southern Ocean scale, suggesting the presence of distinct Zn-biogeochemical regimes in the high- and low-latitude oceans that may relate to differences in physiology, ecology or (micro-)nutrient status. Furthermore, a study of the systematics of both the box model and the OGCM reveals that regional Southern Ocean Zn uptake exerts control over the global Zn distribution via its modulation of the biogeochemical characteristics of the surface Southern Ocean. Specifically, model variants with elevated Southern Ocean Zn:PO4 uptake ratios produce near-complete Zn depletion in the Si-poor surface Subantarctic Zone, where upper-ocean water masses with key roles in the global oceanic circulation are formed. By setting the main preformed covariation trend within the ocean interior, the subduction of these Zn- and Si-poor water masses produces a close correlation between the Zn and Si distributions that is barely altered by their differential remineralisation during low-latitude cycling. We speculate that analogous processes in the high-latitude oceans may operate for other trace metal micronutrients as well, splitting the ocean into two fundamentally different biogeochemical, and thus biogeographic, regimes.